2013
DOI: 10.1371/journal.pone.0080715
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Highly Efficient Regioselective Route to Helicid Esters by Lipozyme TLL

Abstract: Highly regioselective acylation of helicid with fatty acid vinyl esters catalyzed by the lipase from Thermomyces lanuginosus has been successfully performed for the first time. For the enzymatic caproylation of helicid, under the optimal conditions, initial reaction rate was 33.2 mM/h, and substrate conversion and regioselectivity were greater than 99%. In addition, the acyl recognition of the enzyme in the regioselective acylation of helicid was investigated. The results showed that although 6’-O-acyl derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The same phenomenon has already been observed by Zhang et al [35] when carrying out an investigation on esterification of sorbitol and a series of fatty acids (C10—C18) in tert -butanol, catalyzed by Candida sp. 99–125 lipase; Adelhorst et al [11] also observed a faster reaction with the longer fatty acids (C12—C18) compared to the shorter ones (C8—C10) in the solvent-free system, by using a set of lipases from different sources as the catalysts, whereas Yang et al [36] carried out regioselective acylation of helicid with fatty acid vinyl esters in tetrahydrofuran and observed a bell-shaped relationship between the initial reaction rate and the chain length of the vinyl ester.…”
Section: Resultsmentioning
confidence: 99%
“…The same phenomenon has already been observed by Zhang et al [35] when carrying out an investigation on esterification of sorbitol and a series of fatty acids (C10—C18) in tert -butanol, catalyzed by Candida sp. 99–125 lipase; Adelhorst et al [11] also observed a faster reaction with the longer fatty acids (C12—C18) compared to the shorter ones (C8—C10) in the solvent-free system, by using a set of lipases from different sources as the catalysts, whereas Yang et al [36] carried out regioselective acylation of helicid with fatty acid vinyl esters in tetrahydrofuran and observed a bell-shaped relationship between the initial reaction rate and the chain length of the vinyl ester.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the initial reaction rate decreased with further extending chain length from C12 to C16, owing to the higher steric hindrance of the longer-chain acyl donors. Previous studies have found that the biocatalysts from different sources showed different catalytic properties for the different acyl donors due to the specific structure of the lipase active site and the acyl ( Wang and Zong, 2009 ; Yang et al, 2013 ; Li X. F. et al, 2018 ; Yang W. et al, 2019 ). For example, the Pseudomonas aeruginosa cells were more specific toward the medium-chain acyl donors, as well as Candida antarctica lipase B (Novozyme 435) and Thermomyces lanuginosus lipase (Lipozyme TLL) ( Wang and Zong, 2009 ; Yang et al, 2013 ; Yang R. L. et al, 2019 ), while the whole cells of Candida parapsilosis was most efficient for the short chain acyl donor, vinyl propionate.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, Yang et al . also reported a novel and highly efficient regioselective route to helicid esters (Yang et al ., ). This research suggested more possibilities to explore efficient agents ameliorated from helicid.…”
Section: Discussionmentioning
confidence: 99%